N : My Encounter with Racism and the Forbidden Word in an American Classic - Harris, James Henry (Book collections on Project MUSE., 2021)
This book is about a Black man's experience of reading Mark Twain's classic Adventures of Huckleberry Finn for the first time while in graduate school. It captures the author's emotional struggle with Twain's use of the racial epithet more than two hundred times in the text. In these pages, Harris challenges his instructor and classmates and inspires readers to redress the long history of American racism and white supremacy bound up with the N word.